Cone-Beam Computed Tomographic Evaluation of Artifact Effects of Three Different Sealers - Tofangchiha, Maryam; Bolbolian, Marjan; Rahrovan, Sahar; Mirzadeh, Monirsadat; Hajihassani, Neda (Iranian Endodontic Journal, 2018)
Introduction: Cone-beam computed tomography (CBCT) is one of the most important diagnostic tools in maxillofacial imaging. Nowadays different sealers are used in root canal therapy and some of them can create artifact in CBCT images. The aim of this study was to evaluate the effect of different sealers including AH-26, Diadent, and Anyseal in creation of artifact bands in the CBCT images based on voxel size. Methods and Materials: A total of 44 single rooted extracted teeth were selected. The canals were prepared by crown-down technique. All teeth were manually filed up to master apical file (MAF) size 45 and 1 mm shorter than the apical foramen. The teeth were divided into 4 equal groups. The canals were filled with gutta-percha and either of sealers AH-26, Diadent or Anyseal by lateral condensation technique. The control group were filled just with gutta-percha without any sealer. The CBCT images were taken in voxel sizes of 0.3 and 0.15. The Fisher exact and McNemar tests were used for statistical analysis. Results: Although, the control group had the lowest ratio of presence to absence of artifact, the ratio of presence to absence of artifact in voxel size of 0.3 and 0.15 mm were significantly lower in Anyseal than AH-26 (P=0.031, P=0.020) and Diadent (P=0.001, P=0.002). No significant difference was detected between two voxel sizes (P>0.05). Conclusion: In this in vitro study, all evaluated sealers induced artifacts in the CBCT images. Anyseal sealer had the lowest artifact in both evaluated voxel sizes. Keywords: Artifacts; Canal Sealer; Cone-Beam Computed Tomography; Root Canal Filling Material; Root Fracture